If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + I)(4 + -6i) = 0 Multiply (3 + I) * (4 + -6i) (3(4 + -6i) + I(4 + -6i)) = 0 ((4 * 3 + -6i * 3) + I(4 + -6i)) = 0 ((12 + -18i) + I(4 + -6i)) = 0 (12 + -18i + (4 * I + -6i * I)) = 0 (12 + -18i + (4I + -6iI)) = 0 Reorder the terms: (12 + 4I + -18i + -6iI) = 0 (12 + 4I + -18i + -6iI) = 0 Solving 12 + 4I + -18i + -6iI = 0 Solving for variable 'I'. Move all terms containing I to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + 4I + -18i + -12 + -6iI = 0 + -12 Reorder the terms: 12 + -12 + 4I + -18i + -6iI = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 4I + -18i + -6iI = 0 + -12 4I + -18i + -6iI = 0 + -12 Combine like terms: 0 + -12 = -12 4I + -18i + -6iI = -12 Add '18i' to each side of the equation. 4I + -18i + 18i + -6iI = -12 + 18i Combine like terms: -18i + 18i = 0 4I + 0 + -6iI = -12 + 18i 4I + -6iI = -12 + 18i Reorder the terms: 12 + 4I + -18i + -6iI = -12 + 18i + 12 + -18i Reorder the terms: 12 + 4I + -18i + -6iI = -12 + 12 + 18i + -18i Combine like terms: -12 + 12 = 0 12 + 4I + -18i + -6iI = 0 + 18i + -18i 12 + 4I + -18i + -6iI = 18i + -18i Combine like terms: 18i + -18i = 0 12 + 4I + -18i + -6iI = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(6 + 2I + -9i + -3iI) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(6 + 2I + -9i + -3iI)' equal to zero and attempt to solve: Simplifying 6 + 2I + -9i + -3iI = 0 Solving 6 + 2I + -9i + -3iI = 0 Move all terms containing I to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + 2I + -9i + -6 + -3iI = 0 + -6 Reorder the terms: 6 + -6 + 2I + -9i + -3iI = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 2I + -9i + -3iI = 0 + -6 2I + -9i + -3iI = 0 + -6 Combine like terms: 0 + -6 = -6 2I + -9i + -3iI = -6 Add '9i' to each side of the equation. 2I + -9i + 9i + -3iI = -6 + 9i Combine like terms: -9i + 9i = 0 2I + 0 + -3iI = -6 + 9i 2I + -3iI = -6 + 9i The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| z-1.5z-1.5=3(z-4) | | 8x-2=65 | | -3m+6=3-14 | | (4+5i)-(6-2i)= | | 2(x)+2(2x-5)=38 | | 2(x)+2(2x-55)=38 | | 2x^2+2y^2-4x+16y=10 | | 18+2(x+6)=52 | | (5+3i)+(7-8i)= | | 7+x+(x+2)=29 | | 2(3y-4)=20 | | y=x^2+12x+40 | | 6x^2-30x+72=0 | | 5v+3-9v=17 | | 8r^2y+10r^3y^5=2r^2y | | (x-3)(7x+16)=153 | | 2a=-6a-64 | | 2c-8=5c-11 | | 5y^2+30y-35=0 | | C=4x+55 | | 2(10+15)=2(10)+2(15) | | -0.028+20.8= | | 20=14+13(x+8) | | 4x+8=-112-8x | | 8*4=8*4 | | 3t+4=5t-2 | | 2c^2+13c+21=0 | | 2+8=j | | b^2+7b+10=0 | | 3.5I=3 | | 3.6=-1.2h | | 3(3x+2)=14x+4-5x+2 |